COVID-19: Diagnostic Testing and Challenges. Issue 4 (October 2020) - Ogbebor, Osakpolor; Min, Zaw; Cheema, Tariq; Bhanot, Nitin
Abstract : Coronavirus disease-2019 (COVID-19) was declared a pandemic by the World Health Organization on March 11, 2020. Following this, there has been a rapid development in policies and strategies to contain and mitigate the pandemic. One of such strategies involves the development and utilization of testing severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the causative organism of COVID-19. In this article, we explore the diagnostic modalities for COVID-19 based on the available information to date.